Not every photograph is authorial (Novos Olhares, 2016)
The aim of this paper is to contribute to the debate on authorship inphotography, considering some doubts or inaccuracies from commom senseabout the subject, condensed in two provocations: not every photographer is anauthor and not every photograph produced by an author is authorial. We willconsult Michel Foucault, Laura González Flores and Tatiana Salem Levy to aid ourdiscussion, supported by concepts from literature, in which authorship is studiedfor a longer time.